Systematic Literature Review: of Knowledge and Attitude of Mothers Toward Prevention of Diarrhea In Toddlers - Oklan BT Liunokas; Melkisedek Landi; Natalia Debi Subani; Yustinus Ridu; Jesika PR Hanual (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2022)
Diarrhea often attacks children more than adults because their immune system is still weak. This is because knowledge about diarrhea in children is still low so it will affect the attitude of mothers in handling diarrhea in children. The aim is to review the literature to provide more in-depth information and descriptions, ideas to others about mothers' knowledge and attitudes towards preventing diarrhea in children under five. The research method used is a Literature Review of research results related to maternal knowledge and attitudes of diarrhea prevention published in the Google Scholars and Pubmed databases, the articles selected are Indonesian and English articles that were published in 2015 to 2015. by 2021 which can be accessed in full text in Pdf format. From the search data using the google scholar database, 6 articles were found and from Pubmed 4, from 10 articles, it was found that mothers' knowledge and attitudes were still lacking in preventing diarrhea in toddlers. Authors of the journal discussed a lot about the knowledge of mothers' attitudes about diarrhea; the number of samples and the most cross-sectional sample analysis; The author also suggests that mothers always maintain personal and surrounding hygiene, improve toddler nutrition; increase the literature review and increase mother's knowledge about diarrhea.